Toxicity Study of Trichlorfon Insecticide Towards Nile Tilapia Oreochromis sp. - E. Supriyono; P.R. Pong-Masak; P.E. Naiborhu (Jurnal Akuakultur Indonesia)
The study was conducted to study toxicity and accumulation levels of trichlorofon in Nile tilapia (Oreochromis sp.) in weight of 2.54±0.79 g.  Experiment was diveded into three steps, i.e., (1) determination of toxicity range for 48 hours, (2) devinitive test for 96 hours, and (3) bioaccumulation test for 96 hours.  Experiment  was performed using aquaria (volume 10 liter) with semi-static system.  Data was analyzed descriptively and probit test. The results of study indicated that Nile tilapia (8.33%) died after exposuring with trichlorofon 8 ppm for 24 hours, and all fish died when they were exposured with trichlorofon 50 ppm for 18 hours.  LC50 value at 96 hours was 8.52 ppm, while safe concentration levels was 0.43 ppm.  Accumulation rate of tricholorofon in the body Nile tilapia was 0.11% per day.